Implementasi Metode Show And Tell Untuk Meningkatkan Keterampilan Berbicara Siswa Pada Mata Pelajaran Bahasa Indonesia Kelas IV Sekolah Dasar - Rosdiah Salam; Andi Makkasau; Resky Ramadhani, S (JPPSD: Jurnal Pendidikan dan Pembelajaran Sekolah Dasar, 2026)
This study aimed to improve students’ speaking skills in Indonesian language learning through the Show and Tell method in fourth-grade students of SDN 101 Inpres Ujung, Camba District, Maros Regency. This research used Classroom Action Research conducted in two cycles, with each cycle consisting of two meetings. The subjects of this study were the fourth-grade teacher and 9 fourth-grade students. Data collection techniques included observation, oral tests, and documentation. The results showed an improvement in students’ speaking skills as seen in learning activities and speaking skill test results in each cycle. Based on these findings, it can be concluded that the implementation of the Show and Tell method can improve the speaking skills of fourth-grade elementary school students. Theoretically, this study supports learning that involves direct activities and oral communication. Practically, this method can be an alternative for teachers in creating interactive learning to increase students’ confidence, participation, and ability to convey information orally more effectively.